Strangers in a foreign land — developing cultural closure criteria for mines in Australia’s Northern Territory - Smith, H.D. (Mine Closure 2009: Proceedings of the Fourth International Conference on Mine Closure, 2009)
The Northern Land Council is a statutory body created under the Aboriginal Land Rights Act (1976) to protect the rights and interests of traditional Aboriginal landowners. An important part of this work requires the Land Council to deal with appropriate restoration of leased Aboriginal lands following cessation of industrial projects such as mining. This paper seeks to demonstrate that cultural, as well as ecological matters can and should be addressed at closure. Using an example from the Arnhem Land region of Australia’s Northern Territory, it is shown that cultural information is an important factor that can be integrated into the mine site rehabilitation and closure process during the planning phase. When archaeological and anthropological records are supplemented with extant traditional cultural knowledge, it is possible to develop a cultural landscape, or map, that defines locations of special significance. If the location of the mine and its sphere of impacts is referenced against this map specific work required to redress cultural impacts can be undertaken. It is found that by focussing on the physical attributes, ecology and keystone cultural species for each culturally important location, micromanagement of this part of the rehabilitation process is required. This requires links between cultural and ecological knowledge to be defined if the overall cultural integrity of the landscape is to be reconstructed. Outcomes are dependent upon the quality of information that can be recovered, the willingness of traditional custodians to discuss its importance and the extent of damage that has been done.